Saccharide-assisted resolution of bioactive chiral carboxylic acids via NHC-catalyzed regioselective transesterification - Dai, Shuolu (2024)
The utility of unprotected saccharides as chiral auxiliaries in asymmetric synthesis remains largely undeveloped despite their ready availability, configurational diversity, and chiral purity. Here, we disclose an efficient achiral NHC catalytic strategy to regioselectively install racemic α,α-disubstituted carboxylic esters on specific OH groups of saccharides and simultaneously achieve their dynamic kinetic resolution, which makes unprotected saccharides effective chiral auxiliaries. Multiple controlling parameters, including stereoelectronic and steric effects, are employed to ensure regioselectivity amplification and stereodifferentiation. By varying the structures of NHC catalysts, this strategy is suitable for dynamic kinetic resolution of diverse racemic targets by installing them on different OH sites of structurally diverse unprotected saccharides, greatly expanding the application of saccharides in asymmetric synthesis.